The accounting information system impact on micro, small, medium-sized enterprises performances in Bengkulu - Fachruzzaman Fachruzzaman; Rini Indriani; Pratana Puspa Mediastuty; Vika Fitranita; Adista Anbarani Putri Zaman (University of Islam Malang, 2021)
The role of accounting information system (AIS) incorporating to firms' daily operations and management remains indisputable. This paper aims to study the effect of AIS on micro, small, medium-sized enterprises' (MSMEs) financial performance. A total of 522 datasets were gathered from structured questionnaires that were distributed to MSME owners in Bengkulu Province. Partial least squares regression (PLS) was used to build a model for predicting and evaluating the structural model of the study. Similar to the previous study, the result of the study revealed that although the majority of respondents were not implemented AIS properly, they have perceived that AIS has a positive effect on micro, small, and medium enterprises' performances. Moreover, it has also been found that the positive perception of accounting information usages is influenced by accounting resources and the application of basic accounting.